2020
DOI: 10.1016/j.tranon.2020.100828
|View full text |Cite
|
Sign up to set email alerts
|

Combined blockade of EGFR and glutamine metabolism in preclinical models of colorectal cancer

Abstract: Improving response to epidermal growth factor receptor (EGFR)-targeted therapies in patients with advanced wild-type (WT) RAS colorectal cancer (CRC) remains an unmet need. In this preclinical work, we evaluated a new therapeutic combination aimed at enhancing efficacy by targeting cancer cell metabolism in concert with EGFR. We hypothesized that combined blockade of glutamine metabolism and EGFR represents a promising treatment approach by targeting both the “fuel” and “signaling” compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 44 publications
(92 reference statements)
0
20
0
Order By: Relevance
“…Under conditions of nutritional deficiencies, cancer cells can obtain glutamine by breaking down large molecules. For example, excessive activation of the oncogene RAS can promote endocytosis, and cancer cells clear extracellular proteins and degrade into amino acids including glutamine, providing nutrients for cancer cells [72]. In addition to tumor cells, glutamine has a high utilization rate in immune cells to support cell fate determination and immune responses, such as lymphocytes, macrophages, and neutrophils [73][74][75].…”
Section: Glutaminementioning
confidence: 99%
“…Under conditions of nutritional deficiencies, cancer cells can obtain glutamine by breaking down large molecules. For example, excessive activation of the oncogene RAS can promote endocytosis, and cancer cells clear extracellular proteins and degrade into amino acids including glutamine, providing nutrients for cancer cells [72]. In addition to tumor cells, glutamine has a high utilization rate in immune cells to support cell fate determination and immune responses, such as lymphocytes, macrophages, and neutrophils [73][74][75].…”
Section: Glutaminementioning
confidence: 99%
“…In hepatoblastoma cells, circHMGCS1 exerts its oncogenic role by sponging the tumor suppressing action of miR-503-5p, thus upregulating IGF2 and the PI3K-Akt signaling pathway [ 106 ]. In that cancer model, the circRNA/IGF2/Akt axis induced increased expression of the mRNA and protein for glutaminase, an enzyme that converts glutamine to glutamate, which is a major carbon source for ATP production in tumor cells [ 106 , 107 ]. Please refer to Figure 1 for a schematic representation of circRNAs controlling IGF system components in cancer.…”
Section: Novel Regulators Of the Igf System And Their Impact In Camentioning
confidence: 99%
“…The oral glutaminase inhibitor CB-839 was reported to suppress Gln-derived metabolite production during tumor development [84,85]. Cohen et al [86] found that cetuximab (which targets EGFR) in combination with CB-839 improved therapeutic efficacy in cetuximab-resistant CRC (Table 2 and Figure 1D). Gregory et al [87] reported that combining CB-839 with arsenic trioxide or homoharringtonine decreased Gln synthesis in hematologic malignancies, upregulated ROS in the mitochondria, and triggered tumor cell death ( Table 2).…”
Section: Glutamine Metabolismmentioning
confidence: 99%
“…Cohen et al . [86] found that cetuximab (which targets EGFR) in combination with CB‐839 improved therapeutic efficacy in cetuximab‐resistant CRC (Table 2 and Figure 1D). Gregory et al .…”
Section: Amino Acid Metabolismmentioning
confidence: 99%